Effect of performance standard and sex on 24 h ultra-marathon pacing profiles - Chatzakis, P.; Paradisis, G.; Chryssanthopoulos, C.; Zacharogiannis, E. (Journal of Sports Analytics, 2021)
The purpose of the present study was to examine the effect of sex and performance standard on pacing profiles in a 24 h ultra-marathon race. Performance data of 283 participants (237 men and 46 women) from the last decade`s versions (2011 until 2020, with the exception of the 2017 version) of the International Ultramarathon Festival held in Athens-Hellinikon, Greece, were analyzed and pacing profiles were evaluated based on performance standard and sex. Relative speed for every hour and % distance covered in 6 h and 12 h segments and coefficient of variation (CV) were calculated. Mean distance ran was 159.99±36.04 km. Runners followed a reverse J-shaped race pace (p < 0.001). Sex did not seem to interact with pacing (p > 0.05 in every case), while performance standard interacted significantly with pacing (p < 0.001). CV was negatively correlated with total distance covered and total running time (-0.761, p < 0.001 and -0.753, p < 0.001, respectively). In conclusion, the overall pacing profile adopted by runners in a 24 h ultra-marathon race was a reverse J-shaped model, with better runners following a more even pacing than slower runners, with lower velocity variability.